Assessing the impact of remote learning on student engagement: Lessons from global educational responses to crisis - Hafizi, Royyan; Amalia Zubaedah, Putri; Amaliah, Amaliah; Saleh, Muhammad; Chamami, Rikza (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The outbreak of the COVID-19 pandemic has prompted a global shift towards remote learning in education systems worldwide. This study aims to assess the impact of remote learning on student engagement by examining global educational responses to the crisis. Through a qualitative approach and extensive literature review using library research methods, this research explores the lessons learned from various countries' experiences with remote learning during the pandemic. The analysis focuses on key factors influencing student engagement, including access to technology, teacher-student interaction, curriculum adaptation, and socio-economic disparities. Findings reveal both challenges and opportunities associated with remote learning. While technological limitations and digital divide pose significant barriers to student engagement, innovative teaching strategies, collaborative efforts, and flexible curriculum adjustments have emerged as effective solutions. Furthermore, the study identifies the importance of teacher support, parental involvement, and student motivation in enhancing engagement in remote learning environments. The insights gained from this research provide valuable lessons for policymakers, educators, and stakeholders in designing effective strategies to improve student engagement in remote learning settings, both during crises and beyond.